Temperature and tellurium (Te) dependence of electrical characterization and surface properties for a chalcopyrite structured schottky barrier diode - Fiat S.; Bacaksiz E.; Kompitsas M.; Çankaya G. (Elsevier BV, 2014)
Abstract Al/p-CuIn0.7Ga0.3(Se(1−x)Tex)2/Mo Schottky barrier diodes (SBD) have been investigated as electrical and morphological. Electrical characterization and surface maps of the prepared CuIn0.7Ga0.3(Se(1−x)Tex)2 (briefly, CIGSeTe) compounds with two different compositions for x = 0.0 and 0.6 were examined in 150–300 K range. CIGSeTe films were grown on Mo back contact. Some electrical parameters such as, ideality factors, n; zero-bias barrier heights, Φbo and Richardson constants were calculated from the current–voltage (I–V) measurements and plotted as a function of temperature. These results verify that electrical properties of these two diodes can be defined on the basis of the Thermionic emission (TE) theory with the Gaussian distribution (GD) of the Schottky barrier height (SBH) being related to inhomogeneities at the metal/semiconductor (MS) interface. On the other hand, we saw a better morphology in Te rich samples. Rms (root mean square) values increased from 8.50 nm to 9.80 nm with higher pellets on surface with Te.
Keywords: Physical and theoretical chemistry; Electrical properties; Schottky barrier diodes; Φυσική και θεωρητική χημεία; AFM; CIGSeTe